The Effect of Spiritual Self-care Intervention with a Blended Learning Approach on Anxiety in Women with Preterm Labor: A Randomized Controlled Trial - Raziyeh Maasoumi; Farzaneh Dastaran; Fatemeh Faghihiniya; Shima Haghani; Shadi Sabetghadam (Shiraz University of Medical Sciences, 2023)
Background: One way of dealing with pregnancy-related anxiety is through women's beliefs. This studyaimed to assess the effect of spiritual self-care blended learning on anxiety in women with preterm labor.Methods: A non-blinded and parallel randomized clinical trial was conducted in Kashan, Iran, fromApril to November 2018. In this study, 70 pregnant women with preterm labor were randomized tointervention and control groups (35 each) by flipping a coin. For the intervention group, spiritualself-care training was delivered through two face-to-face sessions and three offline sessions. Thecontrol group received routine mental healthcare. The data were collected using socio-demographicinformation and the Persian Short Form of the Pregnancy-Related Anxiety (PRA) Questionnaires.Participants filled out the questionnaires at baseline, immediately after the intervention, and fourweeks after it. Chi-square, Fisher's exact test, independent t-tests, and repeated measures ANOVAwere used to analyze the data. SPSS v.22 was used, with a significance level of P<0.05.Results: At baseline, the mean PRA scores in the intervention and control groups were 52.25±29.23and 49.68±21.66, respectively (P=0.67). There were significant differences immediately after theintervention (28.02±12.13 and 51.42±20.99 in the intervention and control groups, respectively)(P<0.001), and four weeks post-intervention (25.45±10.44 and 52.17±21.13 in the intervention andcontrol groups, respectively) (P<0.001); PRA was lower in the intervention group.Conclusion: Our results revealed the positive effect of spiritual self-care intervention on anxiety inwomen with preterm labor, so this intervention could be integrated into prenatal care.Trial Registration Number: IRCT20160808029255N2